2016
DOI: 10.1073/pnas.1618300114
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, immunological, and clinical features of patients with bacterial and fungal infections due to inherited IL-17RA deficiency

Abstract: Chronic mucocutaneous candidiasis (CMC) is defined as recurrent or persistent infection of the skin, nails, and/or mucosae with commensalCandidaspecies. The first genetic etiology of isolated CMC—autosomal recessive (AR) IL-17 receptor A (IL-17RA) deficiency—was reported in 2011, in a single patient. We report here 21 patients with complete AR IL-17RA deficiency, including this first patient. Each patient is homozygous for 1 of 12 different IL-17RA alleles, 8 of which create a premature stop codon upstream fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
134
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(144 citation statements)
references
References 96 publications
8
134
1
1
Order By: Relevance
“…Furthermore, the protective response was unique to LN cells from previously infected IL-1β -/-mice, since the transfer of LN cells from naive IL-1β -/-mice to naive IL-1β -/-mice had no effect (Supplemental Figure 3). Since Th17 cells and Th1 cells have been implicated in host defense against S. aureus skin infections in humans (4,(10)(11)(12)(25)(26)(27) and mice (15)(16)(17)(18), a role for CD4 + T cells was evaluated using anti-CD4 antibody depletion. Treatment successfully depleted CD4 + T cells from the blood and LNs (91% and 97%, respectively) while not significantly affecting the numbers of CD8 + T cells (Supplemental Figure 4).…”
Section: Protection Of Il-1β-deficient Mice Against S Aureus Skin Rementioning
confidence: 99%
“…Furthermore, the protective response was unique to LN cells from previously infected IL-1β -/-mice, since the transfer of LN cells from naive IL-1β -/-mice to naive IL-1β -/-mice had no effect (Supplemental Figure 3). Since Th17 cells and Th1 cells have been implicated in host defense against S. aureus skin infections in humans (4,(10)(11)(12)(25)(26)(27) and mice (15)(16)(17)(18), a role for CD4 + T cells was evaluated using anti-CD4 antibody depletion. Treatment successfully depleted CD4 + T cells from the blood and LNs (91% and 97%, respectively) while not significantly affecting the numbers of CD8 + T cells (Supplemental Figure 4).…”
Section: Protection Of Il-1β-deficient Mice Against S Aureus Skin Rementioning
confidence: 99%
“…A large homozygous deletion encompassing IL17RA and ADA2 , encoding adenosine deaminase 2, was subsequently identified in two siblings from Sri Lanka with CMC, S. aureus skin infection, and chronic inflammation [25]. Since 2011, AR IL-17RA deficiency, resulting from diverse homozygous nonsense (R66*, Q86*, Q284*, and Y384*), missense (D387N), frameshift indel (H38Afs*15, C57Yfs*5, L90Cfs*30, P257Rfs*16, N440Rfs*50, and Y591Sfs*29), splice site (c.163+1G>A) mutations, and large deletions (770 kb at 22q11.1 ), has been reported in 23 patients from 13 unrelated kindreds originating from Morocco, Turkey, Japan, Saudi Arabia, Algeria, Argentina, and Sri Lanka [25,26]. All patients displayed early-onset (before 6 months of age) CMC affecting mucosal sites (oral thrush and anogenital candidiasis), the skin, scalp, and nails.…”
Section: Chronic Mucocutaneous Candidiasis: Inborn Errors Of Il-17 Immentioning
confidence: 99%
“…In addition, 16 of these patients presented staphylococcal skin diseases (abscesses, folliculitis, furunculosis, and crusted pustules on the face and scalp, sometimes spreading to the shoulders and arms), and 10 patients were prone to recurrent infections of the respiratory tract, including otitis, sinusitis, bronchitis, and lobar pneumonia [25,26]. Consistent with the first report, fibroblasts derived from the skin of the patients did not respond to IL-17A and IL-17F homodimers and heterodimers, whereas no response to IL-25 was detected in their leukocytes, including cells from the patient carrying the only missense D387N mutation with a receptor detectable by flow cytometry at the surface of fibroblasts and monocytes [23,26,27]. We can conclude that IL-17RA plays an essential role in mucocutaneous immunity to C. albicans and, to a lesser extent, to S. aureus , but that it is probably otherwise redundant in host defense (Figure 1, Table 1).…”
Section: Chronic Mucocutaneous Candidiasis: Inborn Errors Of Il-17 Immentioning
confidence: 99%
“…Interestingly, about 30% of psoriatic patients with traumatic spinal cord injury or surgical denervation developed local skin and nail fungal infections visible on the site below the neurological level of damage [103,105]. Since psoriasis is an IL-17-mediated disease and IL-17 immunity is required for antifungal immunity [12,106], the above clinical observations suggest that protection against fungal infections could also depend on neurogenic immunomodulation, as indirectly shown by animal studies demonstrating the function played by nociceptive sensory fibres in co-ordinating IL-17-dependent resistance to C. albicans infections [107]. Further evidence supporting the role played by neurogenic immunomodulation in human psoriasis and atopic dermatitis has been documented in histological studies describing an increased skin innervation in patients in comparison to healthy subjects, as well as an increased expression of sensory neuropeptides and their receptors on immune cells [108,109].…”
Section: Neurogenic T Cell Immunomodulationmentioning
confidence: 99%
“…At times however, T cell plasticity can lead to collateral tissue damage and progression to inflammatory and autoimmune skin diseases or, conversely, to the incapacity of rejecting malignant tissues and clear infections. T helper cells producing IL-17 (Th17) are perhaps one of the most emblematic examples of this dichotomy [11] because, although Th17 responses are required for mucocutaneous immunity against Candida and Staphylococcus infections [12], deregulated IL-17 immunity is associated with skin pathology [13,14,15]. Furthermore, crucial recent findings have shown that, although the skin is the barrier organ most exposed to environmental cues, its molecular composition is rather stable over time and largely dependent on individual characteristics, including dietary habits, gender differences, and stress levels [16,17,18].…”
Section: Introductionmentioning
confidence: 99%